Data on analysis of MK-801 bioavailability in mouse plasma and brain tissue by ultra-performance liquid chromatography-tandem mass spectrometry - Svalbe, Baiba (Data Brief, 2019)
MK-801, a N-methyl-d-aspartate receptor antagonist, is widely used in animal preclinical experiments to induce memory and learning impairments and schizophrenia-like behavior. In the present study, we compared the plasma and brain tissue concentrations of MK-801 after intraperitoneal (i.p.) or subcutaneous (s.c.) administration at a dose of 0.1 mg/kg in male ICR mice. Moreover, these data present the optimization of ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) for the analysis of MK-801 in biological samples. Procedures for the preparation of brain tissue and plasma samples and instrumental analysis are described. This article is related to a research article entitled “Effects of the N-methyl-d-aspartate receptor antagonist, MK-801, on spatial memory and influence of the route of administration” [1].